Selling Expense as a Barrier to Entry - Williamson, Oliver E. (Quarterly Journal of Economics, 1963)
I. Introduction, 112. — II. The selling expense barrier to entry, 113. — III. Probabilistic considerations, 124. — IV. Relevance to the theory of imperfect competition, 127.